"أثر الممارسات الإنتاجية على الاداء التشغيلي للشركات الصناعية العاملة في مدينة الحسن الصناعية في محافظة إربد" (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت هذه الدراسة إلى التعرف على أثر الممارسات الإنتاجية على الأداء التشغيلي للشركات الصناعية العاملة في مدينة الحسن الصناعية في محافظة إربد. واعتمدت هذه الدراسة على المنهج الوصفي التحليلي بأسلوبيه النظري والميداني من خلال توزيع استبانة على عينة بلغت (150) موظفاً يعملون في مستويات إدارية مختلفة في الشركات الصناعية المبحوثة، إذ تم اختيارهم بطريقة عشوائية بسيطة. وتأتي أهمية هذه الدراسة لما للشركات الصناعية من دور فعاّل في تنمية الاقتصاد الوطني والمساهمة في تشغيل أعداد كبيرة من العمالة, إذ تبين من هذه الدراسة أنه يوجد أثر ذو دلالة إحصائية للمتغيرات المستقلة (الممارسات الإنتاجية) على المتغير التابع (الأداء التشغيلي)، مما يشير إلى وجود علاقة ذات دلالة إحصائية بين الممارسات الإنتاجية (التعاون بين العاملين، العلاقة مع الموردين، العلاقة مع الزبائن، وقت التهيئة والإعداد، التنوع في التدريب) والأداء التشغيلي في الشركات الصناعية العاملة في محافظة إربد، في حين لم تصل الممارسات الإنتاجية الأخرى مثل (مدى توافر المواد والتصميم لغايات التصنيع) حد الدلالة الإحصائية. وأشارت النتائج أيضاً إلى عدم وجود فروق ذات دلالة إحصائية في مستوى الأداء التشغيلي في الشركات الصناعية العاملة في محافظة إربد تعزى للمركز الوظيفي. وأشارت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية في مستوى الأداء التشغيلي تعزى لعمر المنشأة ولأسواق الشركة المستهدفة. وقد توصلت الدراسة إلى توصيات عدة منها تطوير العلاقة مع الزبائن والموردين ومحاولة تخفيض أجزاء المنتج خلال مرحلة التصميم وبما يتلاءم مع متطلبات تصنيع المنتج بشكل ينعكس إيجاباً على تكاليف الإنتاج, كما توصي الدراسة أيضاً بالبحث عن الوسائل التي تعمل على تخفيض وقت التهيئة والأعداد للمكائن وجعل أوقات التهيئة وقت خارجي لئلا ۥيعرقل سير عمل المكائن ويساهم في تخفيض الإنتاجية، وتشجيع العمل بروح الفريق الواحد لما للجانب الإنساني في العمل من أهمية في تهيئة بيئة عمل مناسبة تنعكس إيجاباً على مخرجات العمل, وتوصي الدراسة بمواكبة التغيير المتعلق بتكنولوجيا الإنتاج والتي تسهم في الحد من مشاكل التلوث. This study aimed at identifying the production  practices and their effect on the operational performance of industrial companies operating at Al-Hassan qualified industrial zone (QIZ) in Irbed governorate, in order to arrive at results which may contribute to the enhancement of these practices and improving the operational performance of those firms. A descriptive and analytical method were used in both theoretical and field studies by distributing a questionnaires to the sample of the study and analyzing different literature related to the research problem. The sample of this study consisted of 150 employees who belong to different managerial levels and who were selected using simple random method. The results of this research showed that there is a statistically significant effect of  production practices such as cooperation among workers, relationship with suppliers and customers, setup time, and training programs on the operational performance of the selected industrial firms operating in Jordan, while practices such as the availability of raw material and design for manufacturing were not statistically significant. The results showed no significant differences at the level of the operational performance of the researched organizations pertain to managerial position, while results showed significant differences at the level of the operational performance pertainn to the age and target markets of the industrial companies. The study arrived at many recommendations such as: industrial companies must work on the improvement of relationships with customers and suppliers, decreasing the product parts during the designing stage to lower production cost, decreasing machine setup time to minimize idle time, adopting new manufacturing technologies to minimize the pollution level, and searching for more international markets for their industrial products.